(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The field-oriented control (FOC) has been successfully applied to permanently excited linear motors in high-quality drive systems. With this control method, the system kinematics is enhanced, and the upper limits of thrust and acceleration are increased. Accordingly, the accuracy of the position response will be improved. For the FOC method, the stator current control loop of the system plays a major role in the quality of the system. This paper introduces a current vector dead-beat control for Polysolenoid linear motors with fast, accurate, and decoupling characteristics. Numerical simulations demonstrate the advantage of the proposed algorithm.